Synthesis of Novel Thymine-β-lactam Hybrids and Evaluation of Their Antitumor Activity - Piens, Nicola; De Vreese, Rob; De Neve, Nympha; Van Hecke, Kristof; Balzarini, Jan; De Kimpe, Norbert; D’hooghe, Matthias (Synthesis, 2014)
Trimethylene-tethered thymine-β-lactam and thymine-bis-β-lactam chimeras were prepared as novel classes of hybrid systems through selective mono- or bis-N-alkylation of thymine with cis-1-(3-bromopropyl)-β-lactams. In addition, acidic methanolysis of the β-lactam nucleus in these systems provided an entry into the class of thymine-β-amino ester hybrids. A selection of the newly synthesized hybrid compounds was assessed for their antiviral activity, cytotoxicity, and cytostatic activity, revealing a significant cytostatic effect of one of the derivatives against murine leukemia and human T-lymphocyte tumor cells.
Keywords: molecular hybridization; β-lactams; thymine; acidic methanolysis; antitumor agents